Molecular Mechanisms of Neuroinflammation in ME/CFS and Long COVID to Sustain Disease and Promote Relapses - Tate, Warren; Walker, Max; Sweetman, Eiren; Helliwell, Amber; Peppercorn, Katie; Edgar, Christina; Blair, Anna; Chatterjee, Aniruddha (Frontiers in Neurology, 2022)
ME/CFS is a disease now well documented as having arisen commonly from a viral infection, but also from other external stressors, like exposure to agricultural chemicals, other types of infection, surgery, or other severe stress events. Research has shown these events produce a systemic molecular inflammatory response and chronic immune activation and dysregulation. What has been more difficult to establish is the hierarchy of the physiological responses that give rise to the myriad of symptoms that ME/CFS patients experience, and why they do not resolve and are generally life-long. The severity of the symptoms frequently fluctuates through relapse recovery periods, with brain-centered symptoms of neuroinflammation, loss of homeostatic control, ‘brain fog’ affecting cognitive ability, lack of refreshing sleep, and poor response to even small stresses. How these brain effects develop with ME/CFS from the initiating external effector, whether virus or other cause, is poorly understood and that is what our paper aims to address. We propose the hypothesis that following the initial stressor event, the subsequent systemic pathology moves to the brain via neurovascular pathways or through a dysfunctional blood-brain barrier (BBB), resulting in chronic neuroinflammation and leading to a sustained illness with chronic relapse recovery cycles. Signaling through recognised pathways from the brain back to body physiology is likely part of the process by which the illness cycle in the peripheral system is sustained and why healing does not occur. By contrast, Long COVID (Post-COVID-19 condition) is a very recent ME/CFS-like illness arising from the single pandemic virus, Sars-CoV-2. We believe the ME/CFS-like ongoing effects of Long COVID are arising by very similar mechanisms involving neuroinflammation, but likely with some unique signaling resulting from the pathology of the initial SARS-CoV-2 infection. The fact that there are very similar symptoms in both ongoing diseases, despite the diversity in the nature of the initial stressors, supports the concept of a similar dysfunctional CNS component common to both that is controlling the sustaining of the disease state.